Direct quantitative imaging of the writing stage in a photosensitive azopolymer by digital holography. Issue 39 (13th September 2019) - Pagliarulo, V.; Calabuig, A.; Grilli, S.; Ferraro, P.
Abstract : In this paper, we demonstrated that the gradual formation of a surface relief grating (SRG) in azopolymer thin films under continuous light exposure could be directly observed in situ and in real-time, allowing full-field characterization. Abstract : In this paper, we demonstrated that the gradual formation of a surface relief grating (SRG) in azopolymer thin films under continuous light exposure could be directly observed in situ and in real-time, allowing full-field characterization with high spatial resolution. We reported here for the first time, to the best of our knowledge, that digital holography (DH) can be adopted for investigating and monitoring an inscribed holographic surface relief grating (SRG) of azopolymers by two-beam laser interference lithography over a wide area. The writing process could be assessed through quantitative phase imaging (QPI). The reported results show that the proposed method is a truly valuable diagnostic tool that can be useful for investigating the spatial distribution of the writing process, which can eventually contribute to shedding light on the still unclear origin and related mechanism of SRG formation in azopolymers.